Multi-inflammatory syndrome and Kawasaki disease in children during the COVID-19 pandemic: A nationwide register-based study and time series analysis - Koskela Ulla; Helve Otto; Sarvikivi Emmi; Helminen Merja; Nieminen Tea; Peltola Ville; Renko Marjo; Saxén Harri; Pasma Hanna; Pokka Tytti; Honkila Minna; Tapiainen Terhi (WILEY, 2022)
Aim: We investigated whether the ongoing COVID-19 pandemic was associated with the occurrence of Kawasaki disease or with multi-inflammatory syndrome in children (MIS-C).
Methods: This national Finnish register-based study was based on laboratory-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections, MIS-C and Kawasaki disease cases. We performed a time series analysis on the occurrence of Kawasaki disease in 2016-2020.
Results: In 2020, there were 5170 laboratory-confirmed COVID-19 cases in children under 18 years of age and five fulfilled the MIS-C case definition. The occurrence of MIS-C was 0.97 per 1000 (95% confidence interval: 0.31-2.26) laboratory-confirmed SARS-CoV-2 infections in children. Our time series analysis showed that Kawasaki disease cases decreased during the COVID-19 pandemic. The seasonally adjusted incidence rate ratio was 0.49 (95% confidence interval: 0.32-0.74) when it was compared to pre-pandemic levels. This coincided with a reduced occurrence of respiratory infections, due to social distancing in the population.
Conclusion: This nationwide register-based study found that MIS-C was a rare complication of the SARS-CoV-2 infection. The occurrence of Kawasaki disease and respiratory infections decreased during the pandemic. This suggests that transmissible microbes may play an important role in Kawasaki disease and social distancing may have a protective effect.